A Comparative Investigation on Petroleum Demulsification Techniques (Centrifuge and Green Chemicals Versus Conventional Chemicals) - Issaka, Souleyman A.; Nour, A. H.; R. M., Yunus (IJCR, 2015)
The breaking (demulsification) of 50-50% w/o petroleum emulsions of two oils (A and B) by Green (chemical and centrifuge) methods were studied in comparison to conventional (chemical) method. The green methods consisted of silicon based chemical demulsifiers and high-speed centrifuge operated at 12,000 RPM, while the conventional method consisted of Amine group based demulsifiers. In chemical method, the concentrations were varied (0.5%, 1.5% and 3%), while in centrifuge method, the processing time was varied (10 and 30 minutes). The efficiency of these methods was determined by measuring the amount of water separated from the emulsion after being treated. The maximum separation efficiencies for Silicon demulsifiers were 93 and 88% for oils A and B respectively, and that of Amine group demulsifiers were 72 and 86% for oils A and B respectively, While centrifuge demulsification gave maximum separations of 39 and 24% for oils A and B respectively. Based on these results, Silicon based demulsifiers are very effective and reliable method to treat emulsions for different types of oils with different composition, and have the potential to be used as an alternative method in the demulsification or breaking of water-in-crude oil emulsions.